Exploding Head Syndrome among Patients Seeking Help for Tinnitus and/or Hyperacusis at an Audiology Department in the UK: A Preliminary Study - Aazh, Hashir; Stevens, Jennifer; Jacquemin, Laure (Journal of the American Academy of Audiology, 2023)
Background Exploding head syndrome (EHS) is characterized by hearing a sudden loud noise or experiencing a sense of explosion in head during the transition of sleep-wake or wake-sleep. The experience of EHS shares similarities with tinnitus, where an individual perceives a sound without any external sound source. To the authors' knowledge, the possible relationship between EHS and tinnitus has not been explored.Purpose Preliminary assessment of prevalence of EHS and its related factors among patients seeking help for tinnitus and/or hyperacusis.Research Design Retrospective cross-sectional study.Study Sample A total of 148 consecutive patients who sought help for tinnitus and/or hyperacusis at an audiology clinic in the United Kingdom.Data Collection and Analysis The data regarding demographics, medical history, audiological measures, and self-report questionnaires were collected retrospectively from the patients' records. Audiological measures comprised of pure-tone audiometry and uncomfortable loudness levels. The self-report questionnaires which were administered as a part of standard care comprised of the Tinnitus Handicap Inventory, numeric rating scale of tinnitus loudness, annoyance, and effect on life, hyperacusis questionnaire, Insomnia Severity Index, Generalized Anxiety Disorder scale 7, and Patient Health Questionnaire (PHQ-9). To establish presence of EHS, participants were asked “Do you ever hear a sudden, loud noise, or feel a sense of explosion in your head at night?”Results EHS was reported by 8.1% of patients with tinnitus and/or hyperacusis (12 out of 148). The patients with and without EHS were compared, but no significant relationships were found, between the presence of EHS and age, gender, tinnitus/hyperacusis distress, symptoms of anxiety or depression, sleep difficulties, or audiological measures.Conclusion The prevalence of EHS in a tinnitus and hyperacusis population is similar to that in the general population. While there does not seem to be any association with sleep or mental factors, this might be due to the limited variability in our clinical sample (i.e., most patients exhibited high level of distress regardless of EHS). Replication of the results in a larger sample with more variety of symptom severity is warranted.
Keywords: exploding head syndrome; tinnitus; hearing loss; hyperacusis